Interaction and impact of cassava mosaic begomoviruses and their associated satellites - Mollel, Happyness Gabriel (My University, 2014)
Cassava (Manihot esculenta Crantz) is affected by two major viral diseases, namely Cassava brown streak disease (CBSD) and Cassava mosaic disease (CMD). Two of the most widely distributed begomoviruses in East Africa associated with CMD, are East African cassava virus- Uganda2 (EACMV-UG2) and African cassava mosaic virus (ACMV). Despite efforts of generating improved Tropical Manihot Series (TMS) by traditional breeding and using highly resistant geminivirus cassava landraces such as Tropical Manihot Esculenta1 (TME1) and Tropical Manihot Esculenta3 (TME3), more recently two circular single stranded (ss) satellite-like DNA molecules (episomal DNA-II and DNA-III) have been found to be associated with CMD and are able to break resistance to EACMV-UG2 and enhance virus symptoms. The nature of these satellite-like DNA molecules is unknown, and furthermore, the discovery of integration of partial copies of DNA molecules (DNA-II and III fragments), and evidence for transcription from cassava Expressed Sequence Tag (EST) database screening, has led to an even more perplexing disease complex. In the present study, we attempted to further explore the interaction between the satellite-like DNAs and their associated cassava-infecting begomoviruses by investigating the impact of these DNA molecules on disease development in TME3 (tolerant) and cv. 60444 (susceptible) cassava cultivars, and to also gather biological evidence for transcription of integrated genomic and episomal (putative predicted ORFs) sequences in the ACMV and EACMV-UG2-associated DNA-II and DNA-III. Biolistic inoculation of EACMV-UG2, ACMV, and in co-bombardment with DNA-II, DNA-III, DNA-II + DNA-III was successfully performed. CMD symptoms were developed earlier on cassava plants inoculated with ACMV + DNA-II, ACMV + DNA-III, ACMV + DNA-II + DNA-III and EACMV-UG2 + DNA-II, EACMV-UG2 + DNA-III, EACMV-UG2 + DNA-II + DNA-III molecules compared with cassava plants inoculated with begomoviruses alone. Additionally, CMD symptoms were more severe in cv.60444 compared to TME3 when inoculated with begomoviruses alone, or in combination with DNA-II, DNA-III and DNA-II + DNA-III molecules. DNA-II and III were able to break resistance to the highly CMD-tolerant cassava landrace, TME3, and enhance virus symptoms. In order to confirm EST-generated evidence for transcription of DNA-II and III fragments, cDNA was subjected to RT-PCR. RT-PCR of transcripts was successful for only three putative ORFs: ORF C4 of the antisense DNA-II strand, ORF V1 on sense DNA-II strand, and ORF C2 on antisense strand for DNA-III. Primers for transcripts amplified 250 bp and 220 bp for ORF C4 of DNA-II and ORF V1 of DNA-III, respectively. Transcribed ORFs were confirmed by sequencing, and the sequences were similar to the published sequences of Begomovirus associated DNA-II satellite and Begomovirus associated DNA-III satellite, respectively. These results showed that at least two putative ORFs for DNA-II and one (the largest ORF VI) DNA-III can be transcribed. Furthermore, surveys were undertaken in order to ascertain the distribution of episomal and integrated DNA-II and III in cassava germplasm from several countries, namely Tanzania, Uganda, Kenya and Rwanda. Results from this research successfully established genetic diversity and wide geographical distribution of integrated DNA-II and DNA-III molecules. Two primer pairs were designed from a central conserved sequence found in all the integrated DNA-II or III fragments identified from the cDNA libraries (EST database). These primers also amplified integrated sequences of expected size in cassava accessions and wild Manihot species which were similar to satellite-like sequence occurrences in the ESTs. Using designed primers, PCR amplification yielded integrated DNA-II and DNA-III products of ~895 bp and ~306 bp, respectively. Analysis of 363 field leaf samples detected the presence of DNA-II or DNA-III from Kenya (3.3% or 8.3%), Uganda (18% or 2.5%), Rwanda (6.5% or 19.6%) and Tanzania (5.7% or 11.9%) , results which were confirmed by analysis of the sequenced PCR amplicons. Detection of both DNA-II and DNA-III molecules on the samples collected was also found from Kenya (73%), Uganda (69.1%), Rwanda (50%) and Tanzania (69.3%). Interestingly integrated DNA-II and II copies were amplified from healthy, symptomless and infected cassava samples. DNA-II sequences did not vary significantly (93.3% - 99.8%) and were highly similar to the sequences of Begomovirus associated sat DNA-II (AY836366) and 99% with mentha leaf deformity disease associated satellite DNA-II, while DNA-III sequences and Begomovirus associated DNA-II satellite (AY833667). In conclusion, this study has provided useful information that contributes to a further understanding of the biological function of integrated and episomal DNA-II and III molecules in begomoviruses infected cassava plant. However the relationship, if any between episomal and integrated forms needs to be established in future, and investigation into whether the transcribed ORFs can produce functional proteins, needs to be undertaken. How DNA-II and III interact with EACMV-UG2 and ACMV in disease modulation remains to be explored, and the replication of episomal DNA-II and III by these associated begomoviruses needs to be confirmed if these DNA molecules are to truly show a satellite-like relationship. Furthermore, the findings in this study that partial and varied-sized integrated DNA-II and III fragments occur widely in healthy and infected cassava germplasm will enable researchers (plant virologists and breeders) working on cassava in Sub Saharan Africa (SSA) to explore this complex more deeply in order to develop durable management strategies for CMD.
Keywords: Cassava mosaic disease.; Plant viruses.